ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI MINAT SISWA SMA MELANJUTKAN PENDIDIKAN KE PERGURUAN TINGGI - Mohaji Prianggita; Muhammad Abdul Ghofur (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractEducation is one of the essential assets in the development of society and the nation. The low percentage of people who study in Indonesia still needs to be explored. There are many reasons why students do not pursue their education in college. The purpose of this study was to analyze the influence of parents' socioeconomic interactions, self-efficacy, motivation, and student achievement on their interest in continuing education to college. This study uses a quantitative approach. Data was taken from 68 respondents majoring in Social Sciences at SMAN 1 Mejayan. The causal proof analysis performed using multiple linear regression equations. The results of the research prove a positive change in the variables of parents' socioeconomic status, self-efficacy, motivation, and student achievement towards the interest in continuing education. The implications of the results of this study are essential for teachers and school management always to increase student motivation and self-efficacy for students of lower socioeconomic status. Keywords: Socioeconomic Status, Self Efficacy, Motivation, Academic Achievement, Interest.